2020
DOI: 10.1126/science.aaz4304
|View full text |Cite
|
Sign up to set email alerts
|

Sequencing of metals in multivariate metal-organic frameworks

Abstract: We mapped the metal sequences within crystals of metal-oxide rods in multivariate metal-organic framework–74 containing mixed combinations of cobalt (Co), cadmium (Cd), lead (Pb), and manganese (Mn). Atom probe tomography of these crystals revealed the presence of heterogeneous spatial sequences of metal ions that we describe, depending on the metal and synthesis temperature used, as random (Co, Cd, 120°C), short duplicates (Co, Cd, 85°C), long duplicates (Co, Pb, 85°C), and insertions (Co, Mn, 85°C). Three cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
139
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 203 publications
(146 citation statements)
references
References 47 publications
4
139
0
3
Order By: Relevance
“…A very recent work delivered by Yaghi's group has shed light on this issue. [ 274 ] Briefly, atom probe tomography technique—in which sample are sequentially evaporated from the surface by laser pulsing and identified by time‐of‐flight mass spectrometry—has been used for unveiling metal sequences in bimetallic MTV‐MOFs at molecular level. By adjusting the mixing enthalpy (lattice matching of two metals) and configurational entropy (the number of ways for metal arrangement) via controlling the kinds of metals as well as the reaction temperature, diverse metal sequences including random distribution, short/long duplicates, and insertions have been observed.…”
Section: Discussionmentioning
confidence: 99%
“…A very recent work delivered by Yaghi's group has shed light on this issue. [ 274 ] Briefly, atom probe tomography technique—in which sample are sequentially evaporated from the surface by laser pulsing and identified by time‐of‐flight mass spectrometry—has been used for unveiling metal sequences in bimetallic MTV‐MOFs at molecular level. By adjusting the mixing enthalpy (lattice matching of two metals) and configurational entropy (the number of ways for metal arrangement) via controlling the kinds of metals as well as the reaction temperature, diverse metal sequences including random distribution, short/long duplicates, and insertions have been observed.…”
Section: Discussionmentioning
confidence: 99%
“…( C ) Schematic showing the use of atom probe tomography to map the metal sequence in the multivariate MOF samples. Reproduced with permission from the American Association for the Advancement of Science ( 140 ). ( D ) High-resolution TEM image of the junction in an Au─Co─PdSn nanoparticle (scale bar, 3 nm), where the insets show the ADF-STEM image and corresponding EDS element map of the entire nanoparticle.…”
Section: Moving Forward: Opportunities and Challengesmentioning
confidence: 99%
“…3(c)], demonstrating that both random and correlated sequence types emerge naturally from different metal combinations and different synthesis temperatures. 62 While both REDOR-NMR and APT provide very detailed information, they are nonetheless demanding techniques. By contrast, we have found that humble infrared spectroscopy can offer a surprisingly straightforward measure of cation distributions in mixed-metal MOFs and coordination polymers [ Fig.…”
Section: Compositional Disordermentioning
confidence: 99%